PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Abida, Nur (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2020)
This research is motivated by the low mathematics learning outcomes of students of class V A of SD Negeri 136 Pekanbaru, with an average value of 68.25 and of 34 students only 11 students who reach the minimum completeness criteria (KKM). This research is a classroom action research (CAR) conducted aimed at improving the learning outcomes of class A students by applying the Group investigation (GI) type of cooperative learning model. The subjects of this study were class V A students in the 2018/2019 school year. Data collection instruments in this study were teacher activity sheets and student activities and learning outcomes. It can be seen from the results of the implementation of classroom actions carried out 2 cycles, namely the first cycle of students who completed as many as 23 people (67.65%) and students who did not complete 13 people (31.70%), in the second cycle the cycle students completed completely (100 %). There are no more students who receive grades below the KKM. The results showed that the application of the Group investigation (GI) type of cooperative learning model could improve the mathematics learning outcomes of students in class V A of SD Negeri 136 Pekanbaru.